2021
DOI: 10.1002/ppp3.10215
|View full text |Cite
|
Sign up to set email alerts
|

Desert hyacinths: An obscure solution to a global problem?

Abstract: The genus Cistanche Hoffmanns. & Link (Orobanchaceae) includes some 20-30 accepted species native to the Old World, spanning Macaronesia in the west, to north and northwestern China in the east. Typically, the plants occur in deserts, and occasionally coastal dunes or salt marshes, where they are parasitic on the roots of various halophytic shrubs. As nonphotosynthetic holoparasites, all are completely devoid of chlorophyll and functional leaves. They are remarkable in appearance, comprising imposing, brightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Previous studies suggested that the plant mitochondrial electron-transport chain could improve plant performance under stressful environmental conditions [ 29 ]. Unlike C. deserticola and C. salsa , C. tubulosa experience salt stress and cold stress rather than drought stress [ 30 , 31 , 32 ]. This might lead to the duplication of genes in C. tubulosa .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the plant mitochondrial electron-transport chain could improve plant performance under stressful environmental conditions [ 29 ]. Unlike C. deserticola and C. salsa , C. tubulosa experience salt stress and cold stress rather than drought stress [ 30 , 31 , 32 ]. This might lead to the duplication of genes in C. tubulosa .…”
Section: Discussionmentioning
confidence: 99%
“…Cistanche species, as nonphotosynthetic holoparasites, are completely devoid of chlorophyll and functional leaves. They are remarkable in appearance, comprising imposing, brightly colored flowering spikes that sprout seemingly from bare earth, which has earned them their common name ‘desert hyacinths’ [ 4 ]. Some 20–30 accepted species known as the Old World constitute the genus Cistanche , which traverses from the west (Macaronesia) to the east (Northwest China) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are remarkable in appearance, comprising imposing, brightly colored flowering spikes that sprout seemingly from bare earth, which has earned them their common name ‘desert hyacinths’ [ 4 ]. Some 20–30 accepted species known as the Old World constitute the genus Cistanche , which traverses from the west (Macaronesia) to the east (Northwest China) [ 4 ]. Cistanche species grow in deserts, and occasionally coastal dunes or salt marshes, where they are parasitic on the roots of various halophytic shrubs.…”
Section: Introductionmentioning
confidence: 99%
“…However, its use in traditional medicine is not restricted to China, as it has also been used in North African Sahara (Bougandoura et al, 2016 ; Lakhdari et al, 2016 ; Volpato, Saleh, & Di Nardo, 2015 ). The used product is known as “Herba cistanche” and is traded as dried stems of a mix of Cistanche species that are either wild‐harvested or cultivated by growing the host shrubs (Thorogood et al, 2021 ). C .…”
Section: Introductionmentioning
confidence: 99%
“…North African Sahara (Bougandoura et al, 2016;Lakhdari et al, 2016;Volpato, Saleh, & Di Nardo, 2015). The used product is known as "Herba cistanche" and is traded as dried stems of a mix of Cistanche species that are either wild-harvested or cultivated by growing the host shrubs (Thorogood et al, 2021). C. deserticola and C. tubulosa are "cultivated" in China with a harvest of about 6000 tons (Song, Zeng, Jiang, & Tu, 2021).…”
mentioning
confidence: 99%